150k views
1 vote
Solve the following expression when
m = 6 and v= 2
3m - 2v + 11 + v​

User Natu
by
5.5k points

2 Answers

5 votes

Answer:

27

Explanation:

3m - 2v + 11 + v combine like terms

= 3m + (-2v + v) + 11

= 3m - v + 11

substitute m = 6 and v = 2

3(6) - 2 + 11 = 18 - 2 + 11 = 16 + 11 = 27

User Yroc
by
5.0k points
2 votes

Answer:

27

Explanation:

3m - 2v + 11 + v

Combine like terms

3m -v +11

Let m = 6 and v= 2

3*6 - 2 +11

18 -2 +11

27

User Nicbou
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.